2020
DOI: 10.3390/ijerph17217750
|View full text |Cite
|
Sign up to set email alerts
|

Managing Asthma and Obesity Related Symptoms (MATADORS): An mHealth Intervention to Facilitate Symptom Self-Management among Youth

Abstract: Youth with multi-morbidity (one or more chronic diseases) are at increased risk of further morbidity and early mortality as they enter their adult years. Recent increases in both asthma and obesity among youth have led to high health care utilization, increased health related complications, and expanded risks of subsequent cardiovascular disease burden. Common symptoms seen with asthma and obesity include fatigue, pain, depression, and anxiety. These symptoms can result in decreased physical activity, social i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…We anticipate that these results will substantiate the need for targeted care for high-risk asthma patients. Thus, these findings and the knowledge of ED in asthma may have important implications for therapeutic strategies, as severe refractory asthma is a serious problem with high morbidity and mortality in patients and a significant economic burden on healthcare [ 32 ]. Moreover, Makieieva et al reported the dependence of asthma severity on the functional state of the vascular endothelium [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that these results will substantiate the need for targeted care for high-risk asthma patients. Thus, these findings and the knowledge of ED in asthma may have important implications for therapeutic strategies, as severe refractory asthma is a serious problem with high morbidity and mortality in patients and a significant economic burden on healthcare [ 32 ]. Moreover, Makieieva et al reported the dependence of asthma severity on the functional state of the vascular endothelium [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 74% (56/76) of these interventions were mobile based, especially in the last few years. Future studies will focus on a variety of digital interventions, often combining different monitoring tools, such as a diary, lung function measurements, medication adherence, and ACT scores [ 117 , 152 , 197 , 209 , 213 , 285 , 286 ], with a trend toward more automatization in remote monitoring [ 117 , 209 , 213 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, most mHealth apps developed for pediatric patient populations have focused on symptom monitoring and self-management for a wide range of chronic illnesses (Nichols et al, 2020). A symptom monitoring app for children undergoing HCT, TRU-PBMT, was well-liked and utilized by participants on more than half of the days studied (Vaughn et al, 2020(Vaughn et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%